Comparative Outcomes of Mesh versus Non-Mesh Repair in Inguinal Hernia Surgery: A Prospective Clinical Study - Mirzaev Zokirov Xalilovich; Xayitov U. X (American Journal of Biomedicine and Pharmacy, 2025)
Inguinal hernias are among the most frequently encountered conditions in general surgery, often requiring operative intervention to prevent complications such as strangulation or incarceration. Over the past several decades, mesh-based hernia repair techniques have emerged as the gold standard, significantly reducing recurrence rates and improving postoperative quality of life. However, despite the benefits of mesh use, traditional non-mesh suture-based methods remain in practice, particularly in low-resource settings or in patients with contraindications to foreign materials. This prospective clinical study compares the short-term and long-term outcomes of mesh versus non-mesh inguinal hernia repair among patients treated at the Samarkand State Medical University Hospital. A total of 108 patients were enrolled, with 56 undergoing Lichtenstein mesh repair and 52 undergoing traditional Bassini suture repair. Outcomes assessed included operative time, postoperative pain scores, recovery duration, complication rates, and recurrence over a 12-month follow-up period. Results indicate that mesh repair offers superior long-term outcomes, particularly in reducing recurrence, though non-mesh techniques may still have relevance in carefully selected patients.